CRITICAL PEDAGOGY PRINCIPLES FOR DEMOCRATIC INDONESIAN SENIOR HIGH SCHOOL EFL CLASSROOMS - Slamet Wahyudi Yulianto; Muhammad Anjar Nugraha; Anggiana Yulyanti; Diki Rosadi; Noni Trisna Putri; Abdillah Mubarrok Lathief (University of Kuningan, 2026)
There are two primary objectives of this study. First, investigating how the four Critical Pedagogy (CP) principles, consisting of dialog, problem-posing, praxis, and conscientization, are integrated in the Teaching English as a Foreign Language (TEFL) for the purpose of establishing the more Democratic Classroom (DC) and assisting students’ Critical Thinking (CT) development. Second, uncovering the students’ responses toward the integration and what impact they perceive as a result of it. Participants included 213 eleventh-graders from a public senior high school in Subang, West Java, Indonesia. The data were obtained through questionnaire, interviews, and classroom observations from May until October 2025 and were then analyzed through transcribing, coding, categorizing, interpreting, comparing, and concluding. Findings indicate that CP principles are incorporated through ten specific activities designed to foster a DC atmosphere and enhance CT skills. These activities include involving students in classroom decision-making, presenting relevant learning materials, helping students distinguish facts from opinions, and discussing solutions for controversial social issues. Toward the ten activities, the students respond positively and claim that, they are motivated to participate in co-creating classroom decisions and are facilitated in developing their CT skills, including analysis, open-mindedness, and decision-making. The study suggests that EFL teachers should integrate these ten CP-based activities into their daily pedagogical practices. Additionally, it is recommended for policy-makers to promote and support the incorporation of CP principles in TEFL.